Classical Arabic humanities in their own terms : festschrift for Wolfhart Heinrichs on his 65th birthday - Cooperson, Michael.; Heinrichs, Wolfhart. (Middle East and Islamic Studies E-Books Online, Collection 2008, ISBN: 9789004223035., 2008)
The volume brings together approaches to different elements of Arabic-Islamic civilization, mainly in the areas of linguistics, literature, literary theory, and prosody, but also including religion, ritual, economics, and zoology. Contributions also touch upon the adjacent areas of the Old Iranian, Persian, Greek and Byzantine written traditions. Some take as their points of departure specific Arabic words (cat, giraffe) or morphemes; others explore literary genres, subgenres (oration, ode, macaronic poem, travel narrative) or figures within them (the trickster, the devil). Cultural concepts such as wishing, gift-giving or discourse are treated, as are aspects of broader phenomena, such as the role of gender in dream interpretation or the relative merits of luxury goods and mass-produced commodities.